Uterine Transplantation in 2021: Recent Developments and the Future. Issue 1 (March 2022) - Jones, Benjamin P.; Kasaven, Lorraine S.; Chan, Maxine; Vali, Saaliha; Saso, Srdjan; Bracewell-Milnes, Timothy; Thum, Meen-Yau; Nicopoullos, James; Diaz-Garcia, Cesar; Quiroga, Isabel; Yazbek, Joseph; Smith, James Richard
Abstract : Uterine transplantation has evolved rapidly over the last decade. As the number of cases performed increases exponentially worldwide, emerging evidence continues to improve collective knowledge and understanding of the procedure, with the aim of improving both surgical and reproductive outcomes. Although currently restricted to women with absolute uterine factor infertility, increasing awareness as a method of fertility restoration has resulted in a demand for the procedure to be undertaken in transgender women. This manuscript summarizes the recent advances in uterine transplantation, and elaborates further upon the key novel avenues research within the field will focus on over the coming years.